TOMADA DE DECISÃO RACIONAL E EXPERIENCIAL NO PROJETO DE PRODUTOS - Rosa, Valentina Marques da (Universidade de São Paulo. Instituto de Arquitetura e Urbanismo, 2018)
Several studies on decision-making allow us to observe that professionals use one of two systems to define their projects: rational (i.e., inferential or analytical system that operates by rules of reasoning, relatively affect-free) or experiential/ intuitive (i.e., learning or automatic system that is intimately associated with affect). Professionals from creativity related areas may often need to make decisions without much concrete data, which requires the use of their intuition. This paper presents a study that aims to evaluate the reasoning process of making decisions by product designers in comparison to other professionals that work in the same field (i.e., engineers and architects). For this purpose, we used the Rational-Experiential Inventory (REI). Overall, our results show a significant difference between engineers and the other professionals: they make decisions based on a more rational and less experiential system than architects and designers, although we didn’t find huge differences between designers and architects.